Integrating Gamified Learning, Reflection, and One-Minute Silence to Enhance Students’ Subjective Well-Being: A Pre-Post Exploratory Study - Mengkorn Pum (Journal of Research in Education and Pedagogy, 2026)
Student well-being has been recognized as an essential factor in educational success. It has been found to impact academic performance, emotional, social, and cognitive enhancement. The current study examines how a 15-week classroom intervention integrating gamified learning, weekly reflection, and one-minute silent mindfulness affects students’ subjective well-being. The intervention was implemented in a three-hour weekly course. Students completed the subjective well-being questionnaire before the intervention and at the end of the intervention to assess students’ joy of learning, sense of school connectedness, educational purpose, and academic efficacy. The study employed paired-sample t-tests, using Statistical Package for the Social Sciences (SPSS) version 27 to compare pre- and post-intervention mean scores. Findings revealed a statistically significant improvement in joy of learning, academic efficacy, and overall student well-being, with small effect sizes. In the current study, two subjective well-being questionnaire subscales, which are school connectedness and educational purpose, showed positive increases in mean scores; however, these changes were not statistically significant. The findings suggest that the current classroom-based interventions using gamified learning, reflection, and mindfulness may be effective in enhancing students’ emotional engagement with learning and confidence in academic abilities, while relational and purpose-oriented dimensions of well-being may require longer-term or more targeted approaches. The integration of gamification, reflective practice, and brief mindfulness activities is recommended for educators as feasible and low-cost strategies to promote student well-being within regular instructional settings.